2020
DOI: 10.1038/s41467-020-16444-w
|View full text |Cite|
|
Sign up to set email alerts
|

High-resolution annotation of the mouse preimplantation embryo transcriptome using long-read sequencing

Abstract: The transcriptome of the preimplantation mouse embryo has been previously annotated by short-read sequencing, with limited coverage and accuracy. Here we utilize a low-cell number transcriptome based on the Smart-seq2 method to perform long-read sequencing. Our analysis describes additional novel transcripts and complexity of the preimplantation transcriptome, identifying 2280 potential novel transcripts from previously unannotated loci and 6289 novel splicing isoforms from previously annotated genes. Notably,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 49 publications
(80 reference statements)
1
25
0
Order By: Relevance
“…We have combined multiple datasets and applied a strict quality control to generate a comprehensive and highly validated atlas of AS events during pre-implantation development in three mammalian species. Previous studies revealed that AS is very dynamic during mouse pre-implantation development, with most changes in isoform usage occurring at the ZGA 12,[23][24][25] . Our transcriptomic analysis confirms this observation not only for mouse but also for human and cow, despite the marked differences in the relative timing of ZGA in the three species 7,15 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have combined multiple datasets and applied a strict quality control to generate a comprehensive and highly validated atlas of AS events during pre-implantation development in three mammalian species. Previous studies revealed that AS is very dynamic during mouse pre-implantation development, with most changes in isoform usage occurring at the ZGA 12,[23][24][25] . Our transcriptomic analysis confirms this observation not only for mouse but also for human and cow, despite the marked differences in the relative timing of ZGA in the three species 7,15 .…”
Section: Discussionmentioning
confidence: 99%
“…These AS events may generate distinct functional protein isoforms or lead to unproductive mRNA products that are degraded by non-sense mediated decay (NMD), thereby contributing to modulate gene expression 21 . Although proper AS regulation is crucial for post-implantation mammalian embryo development 22 , only a handful of studies have descriptively assessed isoform diversity during pre-implantation stages, concluding that hundreds of genes dynamically express different transcripts in human and mouse, particularly at the maternal-to-zygotic transition 8,12,[23][24][25] . However, the regulatory mechanisms, evolutionary conservation and physiological implications of these patterns are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…GTF files from the three studies were extracted from the GEO database. The two Pacbio long-read technology studies, GSE93848 and GSE138760, were designed to capture long-read transcriptome of various murine tissues (including brain) 23 , and preimplantation embryos 24 , respectively. The NONCODE database (version v6.0) for mouse contains 131,974 long non-coding transcripts 25,26 .…”
Section: Methodsmentioning
confidence: 99%
“…available a series of transcriptomes from a variety of mouse tissues using both short-and long-read sequencing. A compiled transcriptome was derived from three short-read based studies-the first study 20 (GSE125483) includes a variety of mouse tissues (Adrenal, Colon, Heart, Liver, Lung, Muscle, Pituitary, Skin, Thyroid and Brain); the second study 21 (GSE107423) includes healthy brain tissues; and the third study 22 (GSE112348) includes a specific brain region (Cortex)-and two long-read based studies-the first study 23 includes various murine tissues (including brain) (GSE93848) and the second study 24 includes preimplantation embryos (GSE138760). In addition, the NONCODE database for mouse 25,26 , which contains a reference of long noncoding transcripts, was added to the compiled transcriptome ( Supplementary File 3).…”
Section: Comparison Of the Nac Transcriptome To Previous Mouse Annotamentioning
confidence: 99%
“…The genetic mutations within the exon‐intron borders can change the splicing skipping rules and result in multiple genetic diseases 5 . With the development of high‐throughput sequencing, more and more novel splicing isoforms have been discovered in embryo development 4 and disease 5 . In recent years, isoform‐specific functions have been extensively elucidated, and therapeutic targeting of splicing has been considered as an essential strategy for cancer therapy 6,7 .…”
Section: Introductionmentioning
confidence: 99%